Sexual size dimorphism in selected traits of Leptodactylus luctator (Anura: Leptodactylidae) - Salguero, Jerónimo (2024)
Sexual dimorphism reveals a broad variation in morphological, physiological, and behavioral traits related to organismal life strategies. Anurans are particularly suitable for studying the origin, integration, and diversification of sexual dimorphism, owing to the high degree of variation observed in size and secondary sexual characteristics, as well as the diversity of life histories and their complex biphasic cycle. In this study, a morphometric characterization of Leptodactylus luctator is conducted to investigate whether sexual dimorphism is present. A total of 18 variables were measured in the head, body, and limbs of males and females from a population located in wetlands near Ucacha town, Córdoba Province, Argentina. Leptodactylus luctator exhibited more robust limbs in males, but longer fingers in females. Furthermore, females showed a greater axilla-groin length, indicating differences in body shape between sexes in addition to size. Given that larger forelimbs in males have been associated, in the literature, with greater reproductive success, while finger length has been correlated with different levels of circulating sex hormones, the possible selection pressures related to the observed variation are discussed herein.